Impact of Intensive Blood Pressure Therapy on Concern about Falling: Longitudinal Results from the Systolic Blood Pressure Intervention Trial (SPRINT). Issue 3 (28th November 2019) - Berlowitz, Dan R.; Foy, Capri; Conroy, Molly; Evans, Gregory W.; Olney, Christine M.; Pisoni, Roberto; Powell, James R.; Gure, Tanya R.; Shorr, Ronald I.
Abstract : OBJECTIVES: Concern about falling is common among older hypertension patients and could impact decisions to intensify blood pressure therapy. Our aim was to determine whether intensive therapy targeting a systolic blood pressure (SBP) of 120 mm Hg is associated with greater changes in concern about falling when compared with standard therapy targeting an SBP of 140 mm Hg. DESIGN: Subsample analysis of participants randomized to either intensive or standard therapy in the Systolic Blood Pressure Intervention Trial (SPRINT). SETTING: Approximately 100 outpatient sites. PARTICIPANTS: A total of 2313 enrollees in SPRINT; participants were all age 50 or older (mean = 69 y) and diagnosed with hypertension. MEASUREMENTS: Concern about falling was described by the shortened version of the Falls Efficacy Scale International as measured at baseline, 6 months, 1 year, and annually thereafter. RESULTS: Concern about falling showed a small but significant increase over time among all hypertension patients. No differences were noted, however, among those randomized to intensive vs standard therapy ( P = .95). Among participants younger than 75 years, no increase in concern about falling over time was noted, but among participants aged 75 years and older, the mean falls self‐efficacy score increased by .3 points per year ( P < .0001). No differences were observed between the intensive and standard treatment groups when stratified by age ( P = .55). CONCLUSION: Intensive blood pressure therapy is not associated with increased concern about falling among older hypertension patients healthy enough to participate in SPRINT. J Am Geriatr Soc 68:614–618, 2020